Parental history of substance use disorders (SUD) and SUD in offspring: A controlled family study of bipolar disorder. (15th March 2014) - Wilens, Timothy E.; Yule, Amy; Martelon, MaryKate; Zulauf, Courtney; Faraone, Stephen V.
<x xml:space="preserve">Abstract</x> Background and Objectives Adolescents with bipolar disorder (BPD) have been previously shown to be at very high risk for substance use disorders (SUD). We now examine the influence of a parental history of substance use disorders on SUD risk in offspring with and without BPD. Methods We studied 190 parents ascertained through 104 adolescent BPD probands and 189 parents ascertained through 98 control probands using structured interviews. We compared the prevalence of SUD using logistic regression. Results While adjusting for BPD in our combined sample, probands with a parental history of SUD were more likely to have an alcohol use disorder compared to probands without a parental history. Probands with a parental history of SUD were not more likely to have a drug use disorder or overall SUD compared to probands without a parental history. BPD in the offspring did not pose any additional risk between parental history of SUD and offspring SUD. Conclusion Alcohol use disorders were more common in the offspring of parents with a SUD history compared to parents without SUD and the risk was not influenced by offspring BPD. Scientific Significance Clarifying the mechanisms linking parental SUD to offspring SUD, particularly in children and adolescents with BPD, would help clinicians to educate and monitor high‐risk families, which would facilitate strategies to mitigate risks associated with parental substance abuse. (Am J Addict 2014;23:440–446)